Waste Management in Reverse Supply Chain Considering Pricing - Hosseini, Zahra; Fazlollahtabar, Hamed; Mahdavi, Iraj (Review of Industrial Engineering Letters, 2014)
Reverse supply chain problem is one of the concepts in supply chain which as well explore wastes management in relation to customer. In reverse supply chains, wastes are recovered and reproduced leading to profit making of new products which is produced. In this study, residuals, after transferring by costumer, send to production station, sorting station and different manufacturing processes (melting, forging, clamping, painting …) for reproduction. After completion several production processes, diverse products resend to costumers. Here, considering different cost factors and also pricing concept and reproduced parts, the mathematical model of optimizing manufacturing cost is developed. The solution is a useful tool in strategic decision making for municipalities.